2019
DOI: 10.1787/b21e518b-en
|View full text |Cite
|
Sign up to set email alerts
|

Labour share developments over the past two decades

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. │ ECO/WKP(2019)10 LABOUR SHARE DEVELOPMENTS OVER THE PAST TWO DECADES: THE ROLE OF PUBLIC POLICIES UnclassifiedOECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Comparable data for around 2002 suggests that 7% or fewer of dismissals are challenged in court in Australia, Finland, Germany, Ireland, Italy, New Zealand, Norway, the UK, and the US. For Germany, the estimated figure was 23% (OECD, 2004 [35]).…”
mentioning
confidence: 99%
“…Comparable data for around 2002 suggests that 7% or fewer of dismissals are challenged in court in Australia, Finland, Germany, Ireland, Italy, New Zealand, Norway, the UK, and the US. For Germany, the estimated figure was 23% (OECD, 2004 [35]).…”
mentioning
confidence: 99%
“…For instance, see indicator 3.6 in Chapter 3 of OECD (2017[20]) for a summary of indexation rules applying to mandatory earnings-related pensions. See also OECD (2019[23]) for information on the evolution of average gross replacement rates for full-career private-sector workers across different cohorts 4.…”
mentioning
confidence: 99%
“…However, this introduces an awkward circularity: if one motivation for estimating potential output is to anchor demand-side forecasts, then relying on those same forecasts to estimate potential output rather defeats the purpose of the exercise. Moreover, evaluations of OECD forecasting performance have shown that, beyond a 6-month horizon, GDP projections often perform no better than naïve forecasts, are very poor at predicting turning points and are systematically biased upward, all problems shared with other macro forecasters (Pain et al, 2014 [15]; Turner, 2017 [16]). Alleviating the end-point problem using projections would therefore tend to introduce an upward bias into trend labour efficiency projections.…”
mentioning
confidence: 99%
“…The basic logic of the PIM is to sum all past investment while applying a decay factor, the latter encompassing only the scrapping rate (when capital assets are withdrawn from the capital stock at the end of their service lives) when computing the gross stock, a combination of scrapping and depreciation rates when computing the net stock (the 'ageprice' function), or a combination of scrapping and loss of productive capacity when computing the productive stock (the 'age-efficiency' function). 15 The following dynamic equation shows the basic PIM framework:…”
mentioning
confidence: 99%